2021
DOI: 10.1002/jsfa.11161
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and enhanced extracellular overexpression of a new salt‐activated alginate lyase

Abstract: BACKGROUND Alginate lyases (EC 4.4.2.3/4.4.2.11) have been applied to produce alginate oligosaccharides, which have physiological advantages such as prebiotic and antidiabetic effects, and are of benefit in the food and pharmaceutical industries. Extracellular production of recombinant proteins in Escherichia coli presents advantages including simplified downstream processing and high productivity; however, the presence of certain signal peptides does not always ensure successful secretion, which make the extr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…Unlike the fed-batch method required for P. pastoris, PelB-AlyC7 only necessitates glycine supplementation during fermentation. In another study, Meng et al reported the secretory expression of the alginate lyase Aly01 in E. coli, which shares 71.4% sequence similarity with AlyC7 and primarily yields trisaccharides along with small amounts of disaccharides and tetrasaccharides [22]. Aly01's extracellular production was carried out in TB medium supplemented with 1 mM IPTG, 120 mM glycine, and 10 mM CaCl 2 at 18 • C for 48 h, achieving an extracellular activity of 796.3 U/mL after unit conversion [22].…”
Section: Aos Preparation With the Produced Alyc7mentioning
confidence: 99%
See 2 more Smart Citations
“…Unlike the fed-batch method required for P. pastoris, PelB-AlyC7 only necessitates glycine supplementation during fermentation. In another study, Meng et al reported the secretory expression of the alginate lyase Aly01 in E. coli, which shares 71.4% sequence similarity with AlyC7 and primarily yields trisaccharides along with small amounts of disaccharides and tetrasaccharides [22]. Aly01's extracellular production was carried out in TB medium supplemented with 1 mM IPTG, 120 mM glycine, and 10 mM CaCl 2 at 18 • C for 48 h, achieving an extracellular activity of 796.3 U/mL after unit conversion [22].…”
Section: Aos Preparation With the Produced Alyc7mentioning
confidence: 99%
“…In another study, Meng et al reported the secretory expression of the alginate lyase Aly01 in E. coli, which shares 71.4% sequence similarity with AlyC7 and primarily yields trisaccharides along with small amounts of disaccharides and tetrasaccharides [22]. Aly01's extracellular production was carried out in TB medium supplemented with 1 mM IPTG, 120 mM glycine, and 10 mM CaCl 2 at 18 • C for 48 h, achieving an extracellular activity of 796.3 U/mL after unit conversion [22]. Compared with the E. coli strain constructed by Meng et al, strain PelB-AlyC7 also exhibited higher extracellular activity.…”
Section: Aos Preparation With the Produced Alyc7mentioning
confidence: 99%
See 1 more Smart Citation
“…C42 was successfully expressed in E. coli [22]. The alginate lyase Aly01 of PL7 family from Vibrio albicans SK42.001 has been extracellularly expressed in E. coli [23]. Based on the simplicity of purification, the alginate lyase genes also have been expressed in a yeast host.…”
Section: Introductionmentioning
confidence: 99%